102 Prevalence and Predictors of Unrecognized Low Sexual Desire in Men with New Onset Erectile Dysfunction – Findings from a Cross-Sectional, Real-Life Study. (1st May 2022) - Boeri, L; Capogrosso, P; Cazzaniga, W; Candela, L; Fallara, G; Pozzi, E; Belladelli, F; Schifano, N; Cignoli, D; Colandrea, G; Massimiliano, R; Abbate, C; et al.
ABSTRACT: Introduction: The interrelationship between male sexual desire and erectile dysfunction (ED) has been variously investigated. Objectives: We aimed to investigate the prevalence of and the predictors of unrecognized low sexual desire (LSD) in a cohort of men seeking medical help for new onset ED in the real-life setting. Methods: Data from 1509 men seeking first medical help for new-onset ED at a single andrology centre between 01/2010 and 01/2020 were analyzed. Patients were assessed with a thorough medical and sexual history. Comorbidities were scored with the Charlson Comorbidity Index (CCI). All participants were asked to self-report the presence of LSD. Moreover, patients completed the International Index of Erectile Function (IIEF) and the Beck Depression Inventory (BDI). Depressive symptoms were defined as BDI ≥11. The median value of the IIEF-Sexual desire domain (IIEF-SD) was used to categorize the cohort in low SD (IIEF-SD <7) vs. normal SD (IIEF-SD ≥7). The IIEF-Erectile function (IIEF-EF) domain was categorized according to Cappelleri's criteria. Circulating hormones were measured in every patient. Hypogonadism was defined as total testosterone (tT) < 3.0 ng/mL. Descriptive statistics and logistic regression models tested the association between clinical variables and unrecognized LSD. Results: Overall, 312 (20.7%) patients self-reported LSD and were excluded from further analyses. Of 1197 patients not self-reporting LSD, 369 (30.8%) had IIEF-SD <7 (arbitrarily defined as unrecognized LSD). Patients with unrecognized LSD were older [median (IQR) 54 yrs (41-63) vs. 49 yrs (36-59), p<0.001], had lower IIEF-EF [10 (5-20) vs. 22 (11-28)] but higher BDI [6 (3-12) vs. 4 (1-8)] and lower tT [4.3 (3.2-5.7) vs. 4.7 (3.2-7.3) ng/ml] (all p<0.001) than men without LSD. Overall, men with unrecognized LSD presented a higher rate of severe ED (50% vs. 24%, p<0.001), and of BDI suggestive for depressive symptoms (30.6% vs. 18.3%) and of hypogonadism (19.9% vs. 10%) (all p<0.001). At multivariable logistic regression analysis, lower tT, despite not suggestive for hypogonadism (OR 0.91, p=0.03), lower IIEF-EF (OR 0.94, p<0.001) and BDI suggestive for depressive symptoms (OR 1.83, p<0.001) were found to be independent predictors of unrecognized LSD, after accounting for age. Conclusions: One out of three men seeking first medical help for ED showed unrecognized LSD according to the IIEF-SD domain scores. Men with unrecognized LSD were older, had higher rates of severe ED and depressive symptoms and lower tT values despite not suggestive for hypogonadism than men with normal SD. A detailed investigation of sexual desire should be always included in the diagnostic work-up of men with ED, in order to better tailoring patient therapeutic management. Disclosure: Work supported by industry: no.